SPATIAL HARMONIZATION THROUGH BIOPHILIC TRANSITIONAL SPACES MULTI-STAGE SENIOR HOUSING ANALYSIS STUDY - Rasyita Atmoko; Suzanna Ratih Sari (Journal of Architecture & Environment, 2026)
In Indonesia, developing senior housing often takes multiple years because of financial constraints and the lack of a comprehensive plan. While this strategy allows for a stepwise improvement in the available infrastructure, it may lead to disjointed spatial configurations and uneven quality in the surrounding environment. In many cases, the absence of adequate transitional spaces has been shown to result in limited accessibility, reduced social interaction among senior residents, and weak visual and physical connections to the outside space. This study explores the role of biophilic-based transitional spaces in supporting spatial integration and improving the environmental quality of gradually developed senior housing. A case study was conducted at the Wisma Lansia Harapan Asri in Semarang. Qualitative spatial analysis was conducted through phenomenological observation to capture environmental experience. Transitional areas play an instrumental role in providing linkages between residential blocks, circulation zones, and external environments. Designing micro gardens, corridor recesses, courtyard social gardens, and gardens as buffers reinforce spatial continuity while balancing enclosure and social permeability. Such evidence has helped evaluate and refine spatial design principles in multiple housing types, including pavilions and class-setting units, aimed at improving the ambience, comfort and psychosocial health of senior residents. Design recommendations for pavilion and class-setting units refine these principles, offering flexible, non-technical criteria for architects to improve ambience comfort and psychosocial health. By addressing user experiences and environmental quality, biophilic transitional spaces enable stepwise infrastructure improvements without compromising livability, providing a model for adaptable senior housing designs.